El golpe de Estado del 11 de abril en Venezuela y sus causas - López Maya, Margarita (Sociedad y Economía, 2002)
Civil participation in the coup and counter-coup of April 2002 plays a key role for the understanding of the Venezuelan situation. After two decades of economic recession and social impoverishment an acute polarization has resulted within that society. Such polarization found ways of political expression in the 1990’s through projects that were reluctant to mutual acknowledgement, due to the fact that the very rules of the political game were at stake. This entails that, although the April coup d’Etat has been superseded, the crisis is still open, as well as the conspirating and authoritarian temptations.